2021
DOI: 10.3390/atmos12070908
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach for the Analysis of Deep Convective Events: Thunderstorm Intensity Index

Abstract: In this study, an investigation of a new thunderstorm intensity index (TSII) derived from lightning data is performed, along with its relationship to rain, wind, hail and waterspouts as well as instability indices (CAPE, LI, KI, and DLS). The study area is located in the northeastern Adriatic and includes various terrain types in a relatively small area (coastal, flatlands, hills and valleys, and mountain regions). The investigated period covers 11 years (2008–2018). The mathematical algorithm standing behind … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 52 publications
(94 reference statements)
0
4
0
Order By: Relevance
“…Further, to assess the ability of LPI to reproduce the observed lightning activity, lightning data from the Lightning Detection Network (LINET) (Betz et al, 2009) (Franc et al, 2016), showing significant improvement in the sensitivity detection toward smaller stroke current amplitudes. For most of the European region (Franc et al, 2016;Jelić et al, 2021), the average minimum detectable signal is 0.7 kA, and the median location accuracy error is ±84 m. Here, we considered total lightning information, i.e., we did not differentiate between types or polarities of lightning flashes as LPI presents the overall potential for lightning activity without preferences to the type or polarity of lightning discharges. The total lightning for the examined cases was taken from the 2D database of lightning flashes at a 3 km x 3 km horizontal and 2 min temporal resolution (developed by Jelić et al, 2021) over the domain shown in Figure 1a.…”
Section: Datementioning
confidence: 99%
“…Further, to assess the ability of LPI to reproduce the observed lightning activity, lightning data from the Lightning Detection Network (LINET) (Betz et al, 2009) (Franc et al, 2016), showing significant improvement in the sensitivity detection toward smaller stroke current amplitudes. For most of the European region (Franc et al, 2016;Jelić et al, 2021), the average minimum detectable signal is 0.7 kA, and the median location accuracy error is ±84 m. Here, we considered total lightning information, i.e., we did not differentiate between types or polarities of lightning flashes as LPI presents the overall potential for lightning activity without preferences to the type or polarity of lightning discharges. The total lightning for the examined cases was taken from the 2D database of lightning flashes at a 3 km x 3 km horizontal and 2 min temporal resolution (developed by Jelić et al, 2021) over the domain shown in Figure 1a.…”
Section: Datementioning
confidence: 99%
“…With continuous improvements of the LINET network, the median values of detected current amplitude values had decreased by half from 2009 (Franc et al., 2016), showing significant improvement in the sensitivity detection toward smaller stroke current amplitudes. For most of the European region (Franc et al., 2016; Jelić et al., 2021), the average minimum detectable signal is 0.7 kA, and the median location accuracy error is ±84 m. Here, we considered total lightning information, that is, we did not differentiate between types or polarities of lightning flashes as LPI presents the overall potential for lightning activity without preferences to the type or polarity of lightning discharges. The total lightning for the examined cases was taken from the 2D database of lightning flashes at a 3 km × 3 km horizontal and 2 min temporal resolution (developed by Jelić et al., 2021) over the domain shown in Figure 1a.…”
Section: Selected Hailstorms and Observational Datamentioning
confidence: 99%
“…The main objective of this study is to evaluate the convective episodes based on METAR and SPECI data collected from 17 Romanian airports from 2012 to 2022. Extensive Although convective events have a great spatiotemporal variability, climatological studies can provide valuable information in respect to their spatial and temporal differences in a particular region, as well as providing trends on various time-scales [34,35]. Based on climatological scientific results, the user can anticipate important changes in local or regional weather, as well as severe weather associated with convection events [29].…”
Section: Introductionmentioning
confidence: 99%